2011
DOI: 10.1002/eqe.1097
|View full text |Cite
|
Sign up to set email alerts
|

Full‐scale shaking table test for examination of safety and functionality of base‐isolated medical facilities

Abstract: A series of full-scale shaking table tests are conducted using the E-Defense shaking table facility on a base-isolated four-story RC hospital structure. A variety of furniture items, medical appliances, and service utilities are placed on the hospital specimen in as realistic a manner as possible. Four ground motions are adopted, including recorded near-fault ground motions and synthesized long-period, long-duration ground motions. The test results show that the base-isolated system performed very effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 12 publications
0
94
0
1
Order By: Relevance
“…Thus, the effectiveness of seismic isolation to protect a variety of building content was evaluated directly, rather than by speculation of the influence of recorded responses, such as floor accelerations. In fact, the primary objective of the hospital test program [90] was to examine the performance of hospital equipment, and evaluation of the seismic performance of interacting partition walls, suspended ceilings, and sprinkler piping was a key component of the NEES/E-Defense tests [91]. Second, full scale models are required to realistically reproduce the effects of vertical vibration of the floor system and thus assess the influence of vertical excitation on building content.…”
Section: Experimental Demonstrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effectiveness of seismic isolation to protect a variety of building content was evaluated directly, rather than by speculation of the influence of recorded responses, such as floor accelerations. In fact, the primary objective of the hospital test program [90] was to examine the performance of hospital equipment, and evaluation of the seismic performance of interacting partition walls, suspended ceilings, and sprinkler piping was a key component of the NEES/E-Defense tests [91]. Second, full scale models are required to realistically reproduce the effects of vertical vibration of the floor system and thus assess the influence of vertical excitation on building content.…”
Section: Experimental Demonstrationmentioning
confidence: 99%
“…Recently, two independent test programs on full scale isolated buildings with weights of 5,000-10,000 kN have been conducted at National Institute for Earth Science and Disaster Prevention (NIED) E-Defense shaking table of Japan. The first of these test programs evaluated the response of a 4-story R/C hospital building isolated with 4 high damping rubber bearings and 4 natural rubber bearings paired with steel dampers [90]. The second of these test programs, a NEES/E-Defense collaboration, evaluated the response of a 5-story steel moment frame building isolated with (1) 9 triple pendulum bearings (TPBs); and (2) 4 lead-rubber bearings (LRBs) paired with 5 cross linear bearings (CLBs).…”
Section: Experimental Demonstrationmentioning
confidence: 99%
“…The test results indicated that the baseisolated system effectively mitigated the damage to hospital components against near-fault ground motions, but dangerous movement of unanchored sliding or rolling equipment was observed during long-period ground, long duration motions. Further information from this test program is available in Sato et al (2011).…”
Section: -26 6: Simulated Seismic Testing Of Gcr 17-917-44 Nonstructmentioning
confidence: 99%
“…The building superstructure was the same as that tested by Sato et al (2011). However, this test building was outfitted as a medical facility with a wide variety of hospital contents to investigate the effects of vertical response on building contents and nonstructural components.…”
Section: -26 6: Simulated Seismic Testing Of Gcr 17-917-44 Nonstructmentioning
confidence: 99%
“…A number of recent research works that extend the simulation in the more realistic 3D space [10][11][12][13][14][15][16][17][18][19] have been reported. Matsagar and Jangid [10] investigated the seismic response of a single-story asymmetric structure supported on various base-isolation systems during impact with adjacent structures.…”
Section: Introductionmentioning
confidence: 99%